A Socially-Aware Perspective to Understand and Fight Violence against Children and Adolescents - Silva Júnior, Deógenes P. da; Baranauskas, M. Cecília C.; Pereira, Roberto (Anais do Workshop sobre as Implicações da Computação na Sociedade (WICS); 2022: Anais do III Workshop sobre as Implicações da Computação na Sociedade, 2022)
In challenging design contexts, such as the violence against children and adolescents, considering human values is critical as they influence people's social and cultural lives. Considering values when understanding a social problem is not a trivial activity due to the difficulty of working with abstract concepts, the complexity of people's lives, and the lack of artifacts and recommendations to support designers in this task. Drawing on the Socially Aware Design, this paper describes the use of value-oriented artifacts to understand the problem and to identify requirements for systems design against child violence. As a result, the problem of child violence is characterized in a socially-aware manner, and propositions of value-oriented requirements for a solution are raised.